PENGARUH KOMISARIS WANITA TERHADAP HUBUNGAN ANTARA EKSEKUTIF WANITA DAN KEPUTUSAN PENDANAAN PERUSAHAAN - Sudarsi, Sri; Sudiyatno, Bambang; Nuswandari, Cahyani; Kusuma Putri, Galuh (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research will test the influence of female executives on funding decisions with female commissioners as a moderating variable, using research objects of companies in Indonesia and listed on the Indonesian Stock Exchange. This research will further explore research conducted by Datta et al. (2021), where they use data from companies in America which have a different culture from Indonesia. This research uses a female board of commissioners as a moderating variable, due to differences in company management structures. This research uses the Ordinary Least Squares method with a sample of 364 non-financial companies during the 2017–2021 period. The test results show that female executives have no effect on the proportion of debt, both short-term and long-term. Female commissioners weaken the relationship between female executives and the proportion of short-term debt, but strengthen the relationship between female executives and the proportion of long-term debt. For company management, the results of this research can be used as a guide for decision-making regarding funding and the selection of top management. This research could be a reference for future researchers and trigger further research on this topic.